2021
DOI: 10.1101/2021.09.06.21262839
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

On-scalp magnetoencephalography for childhood epilepsies

Abstract: Magnetoencephalography (MEG) is an established method to investigate epilepsy. Current MEG systems house hundreds of cryogenic sensors in a rigid, one-size-fits-all helmet, which results in several limitations, particularly in children. On-scalp MEG based on optically-pumped magnetometers (OPMs) may alleviate these limitations. We report on five children (5-11 years old) with self-limited focal (n=3) or structural (n=2) epilepsy who underwent cryogenic (102 magnetometers) and on-scalp (32 OPMs) MEG. We compar… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…This provides a certain degree of confidence that our OP-MEG recordings could be useful for delineating the epileptogenic zone and supports the need for studies in larger numbers of patients with surgical outcome data. Additionally, and reassuringly, Feys et al, (2021) have shown a direct and compelling comparison between OPM and SQUID recordings in the estimated epileptogenic zone in 5 children with epilepsy.…”
Section: A) B) C)mentioning
confidence: 78%
See 2 more Smart Citations
“…This provides a certain degree of confidence that our OP-MEG recordings could be useful for delineating the epileptogenic zone and supports the need for studies in larger numbers of patients with surgical outcome data. Additionally, and reassuringly, Feys et al, (2021) have shown a direct and compelling comparison between OPM and SQUID recordings in the estimated epileptogenic zone in 5 children with epilepsy.…”
Section: A) B) C)mentioning
confidence: 78%
“…This means that it is possible to capture maximal signal for any head-size. This can increase the SNR of observed interictal epileptiform discharges (Feys et al ., 2021) and it has been shown with high-T C on-scalp SQUID-MEG, that higher proximity of the sensors to the scalp can increase the number of interictal discharges that are observed (Westin et al ., 2020). This improvement would be particularly important for children, due to their smaller head size (Boto et al ., 2016; Hill et al ., 2019) and is pertinent for epilepsy since there is an incidence peak in childhood (Kotsopoulos et al ., 2002; Fiest et al ., 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…MEG can be particularly helpful in cases of frontal lobe epilepsy that masquerade as a generalized epilepsy on the scalp EEG recording. 12 It also has distinct advantages in identifying seizures of deep tissue onset.…”
Section: Utilitymentioning
confidence: 99%
“…Identifying the irritative zone helps epileptologists and neurosurgeons plan surgeries with good hypotheses in order to create the best possible blueprint to obtain meaningful information from invasive recording. MEG can be particularly helpful in cases of frontal lobe epilepsy that masquerade as a generalized epilepsy on the scalp EEG recording 12 . It also has distinct advantages in identifying seizures of deep tissue onset.…”
Section: Introductionmentioning
confidence: 99%